Communication, Manipulation, Seduction: The Pragmatics of Transparency - Parret, Herman (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2022)
Communicative interaction is never fully transparent. A definition in terms of pure transfer of information is an impoverishment of the semantic content of a message. Other emotional connotations of linguistic interaction are deeply rooted into the depth of the psychology of subjects. This means that the interaction is often manipulatory and even seductive. This paper tries to present in a more systematic way the conditions of manipulatory and seductive discursive production. Speech acts theory (Austin, Searle) and conversational logic (Grice) offered some tools to formalize more or less these subtle production conditions of non-transparent “communication”.